Knowledge, attitude and practice towards sexually transmitted diseases amongst the inmates of women shelters homes at Klang Valley - Noraziah Mohamad Zin; Ismarulyusda Ishak; Kasturi Manoharan (BMC, 2019)
Abstract Background Previous studies show that there is a changing trend of sexual and reproductive behaviour among youth and this requires more attention and awareness especially on sexually transmitted diseases (STD). This study was carried out to evaluate the knowledge, attitude and practice of sexually transmitted diseases among selected inmates of women shelter homes. Methods A cross-sectional study was carried out by involving 60 participants whom aged in between 13 to 25 years old. The questionnaires were developed in 'Bahasa Melayu' and it has been anonymous guided questionnaires. Results The result showed that the mean age of the participants was 17.9 years old and most of the participants have completed secondary school (91.7%). Overall, the level of knowledge of participants on STDs were classified into three groups; 'high knowledge' (33.3%), 'medium knowledge' (35.0%) and 'low knowledge' (31.7%). The majority have heard of HIV/AIDS (95%) but with respect to other STDs was less well known. Whereas, the mean score for attitude was 23.1 out total 25. Their knowledge level was not influenced by their age (p = 0.61) and socio-economic status (p = 0.85). However, their attitude was influenced by their age (p < 0.05). Conclusion Knowledge on non-HIV STDs is still lacking and risky behaviours have been practiced. Although there were high level of knowledge and attitude among them but their practice on sexuality contradicts it especially on contraceptive use and pre-marital sex.